Chemogenetic enhancement of functional recovery after a sciatic nerve injury - Jaiswal, Poonam B (Eur J Neurosci, 2017)
Designer receptors exclusively activated by designer drugs (DREADDs) are chemogenetic tools used to modulate neuronal excitability. We hypothesized that activation of excitatory (Gq) DREADD by its designer ligand, clozapine-N-oxide (CNO), would increase the excitability of neurons whose axons have been transected following peripheral nerve injury, and that this increase will lead to an enhanced functional recovery. The lateral gastrocnemius (LG) muscle of adult female Lewis rats was injected unilaterally with AAV9- hsyn- hM3Dq-mCherry (7.6×10(9) viral genomes/μl) to transduce Gq-DREADD expression in LG neurons. The contralateral LG muscle served as an uninjected control. No significant changes in either spontaneous EMG activity or electrically evoked direct muscle (M) responses were found in either muscle after injection of CNO (1mg/kg, i.p.). The amplitude of monosynaptic H-reflexes in LG was increased after CNO treatment exclusively in muscles previously injected with virus, suggesting that Gq-DREADD activation increased neuronal excitability. After bilateral sciatic nerve transection and repair, additional rats were treated similarly with CNO for up to three days after injury. Electrophysiological data were collected at 2, 4 and 6 weeks after injury. Evoked EMG responses were observed as early as 2 weeks after injury only in Gq-DREADD expressing virus injected LG muscle. By 4 weeks after injury, both M-response and H-reflex amplitudes were significantly greater in muscles previously injected with viral vector than contralateral, uninjected muscles. Increases in the excitability of injured neurons produced by this novel use of Gq-DREADD were sufficient to promote an enhancement in functional recovery after a sciatic nerve injury.